UTILIZATION OF CHITOSAN EDIBLE COATING FROM WHITELEG SHRIMP (Litopenaeus vannamei) WASTE ON THE SHELF LIFE OF SALTED EGGS - Talitha Nabilah; Sakinah Haryati; Bhatara Ayi Meata (Universitas Mataram, 2026)
Salted eggs are eggs preserved by salting. A common problem faced by salted egg producers is their short shelf life. This study aims to determine the best concentration of whiteleg shrimp chitosan as an edible coating in maintaining the quality of salted eggs during room temperature storage. This study used a completely randomized design (CRD)two replications with shrimp chitosan concentrations consisting of 0%, 2%, 4%, and 6% with a storage period of 28 days. The method used in this study was a laboratory-scale experimental method. This study was conducted in three stages: making the edible coating, coating, and storing the salted eggs. Shrimp chitosan edible coating was characterized by a viscosity test. Salted eggs that had been coated with chitosan edible coating were tested for weight loss, organoleptic, proximate, TPC (Total Plate Count), and Bayesian test. Based on the results of the study, the best treatment was at a chitosan concentration of 6% with an aroma value of 5.98; texture 6.03; color 5.55; and taste 5.57. The proximate test of salted eggs from the best treatment contained water content of 52.59%, protein 13.42%, fat 19.83%, and ash 2.84%. The weight loss test of the best treatment was 0.005% and the TPC had a value of 1.55×103 CFU/g at the end of storage.